Inflation, output growth and their uncertainties: A multivariate GARCH-M modeling evidence for Nigeria - Perekunah B. Eregha; Arcade Ndoricimpa (African Governance and Development Institute (AGDI), 2019)
The study applies a BEKK GARCH-M model to examine the effect of uncertainty on the levels of inflation and output growth in Nigeria. The results suggest a significant positive effect of inflation uncertainty on the level of inflation, supporting the Cukierman and Meltzer (1986) hypothesis. In addition, uncertainty about inflation is found to be detrimental to output growth, supporting the Friedman's (1977) hypothesis of a negative effect of inflation uncertainty on output growth. Uncertainty about growth does not have a significant effect on both the levels of inflation and output growth. The evidence in this study suggests that Nigeria should put in place policies minimizing inflation uncertainty to avoid its adverse effects on the economy. In addition, the independence relationship between output growth and its uncertainty in Nigeria suggest that they can be treated separately as suggested by business cycle models.
Keywords: C22; E0; 330; Inflation; Inflation Uncertainty; Output; Output Uncertainty; BEKK GARCH-M